OPTIMIZATION OF DIKMAS LANTAS FOR STUDENTS THROUGH POLICE GOES TO SCHOOL TO PREVENT TRAFFIC VIOLATIONS IN THE JURISDICTION OF THE BREBES POLICE: OPTIMIZATION OF DIKMAS LANTAS FOR STUDENTS THROUGH POLICE GOES TO SCHOOL TO PREVENT TRAFFIC VIOLATIONS IN THE JURISDICTION OF THE BREBES POLICE - ERLANG SURYA (Advances in Police Science Research Journal, 2022)
ABSTRACT OPTIMIZATION OF DIKMAS LANTAS FOR STUDENTS THROUGH POLICE GOES TO SCHOOL TO PREVENT TRAFFIC VIOLATIONS IN THE JURISDICTION OF THE BREBES POLICE ERLANG SURYA AGUSTIAN, 18.130, erlangsurya10@gmail.com A traffic violation alone is a problems it often happens in. in road Traffic Law no 22 years 2009 is undang-undang who set about traffic and public transport, therefore it was mentioned in undang-undang such that a traffic violation to be regulated in the undang-undang.On the related offences on, like the existing problems in the jurisdiction of brebes police released jateng.tribun.news is traffic offenders during an operation abiding in brebes in 2019 935 people. The research literature is that research done by means of, literature with a good, , book or report. penilitian has been done beforeIn this research, writer conducted a study using multiple theory and the concept is, so as to be understood literature and the results of research with the problems and optimize dikmas. for learners A general picture of traffic police brebes brebes is implementing regional police from the police central java area and placed under the control. head of central java, It is based on section 1 to 5 regulation the chief of inp number 23 years 2010 date 30 september 2010 about organisational hierarchy and work procedure of the police a resort and sector police. Drawing conclusions based on the research and discussions that were analyzed with the Dikmas then for the student through police goes to school to prevent a traffic violation under city police Brebes. Then we can conclude is the implementation of Dikmas then to scholars have not optimal for the lack of capability owned personnel and facilities prasrana inadequate and had no policy support the implementation of the relevant organisations Dikmas then to students besides the implementation of activities Dikmas in 2021 more performs activities in order to prevent the spread of covid-19 not Dikmas activities on the education about traffic good and right to students. To optimize the implementation of Dikmas then so can be done by applying for the evaluation management theory. Keywords : Optimization, Dikmas Lantas, Police Goes to School